The Development of Hamka Islamic Thought - *Muhammad Haikal; Teuku Kusnafizal; Teuku Abdullah (Universitas Syiah Kuala, 2021)
This study aims to find and describe the biography and thought of Hamka. This research uses historical methods using a qualitative descriptive approach. The data collection techniques used are library studies and documentation. Hamka is a unique intellectual figure. The uniqueness ofa lies in the fact that although it is a product of traditional educational institutions, it nevertheless has generalistic and modern insights. Hamka is an intellectual figure (modernist) who is always concerned about seeing various problems of the people and through his various writings, Hamka seeks to